Pengukuran Kesuksesan Pendidikan Inklusif: Pengembangan Indikator Kinerja dan Evaluasi - Muhammad Firman; Muhammad Fajar Firdausyi; Sobali Suswandy; Denden Rusdiana (Departement of Mathematics Education, 2021)
This study was carried out because of the importance of studies related to inclusive education. This research was conducted based on secondary reference sources in the form of theories, concepts and results of previous research publications which were analyzed scientifically to answer various problems in this research. The findings of the research conducted found that inclusive education can be interpreted as a commitment to providing equal education for all students. To measure the success of inclusive education, there needs to be good performance indicators and an effective evaluation system. In this way, we can ensure that every student, including those with special needs, has a fair opportunity to thrive and succeed in their education. Good evaluation also enables continuous improvement in efforts to realize better inclusive education for all. Several recommendations for improving inclusive education based on the findings and implications of studies measuring the success of inclusive education: 1) Strengthening Teacher Training; 2) Development of More In-Depth Performance Indicators; 3) Parent and Student Involvement; 4) Adequate Resource Allocation; 5) Information Systems Development; 6) Development of an Inclusive School Culture; 7) Changes in Policy and Practice; 8) Continuous Evaluation; 9) Providing Special Support; 10) Community Education.